Methodological approaches to assessment of the human capital value in condition of social modernization - Chulano, Zaure; Ussenova, Anel (Journal of International Economics and Management, 2015)
Social and modernization process involves the expansion of use of industrial and innovative technologies based on the use of human capital and scientific knowledge. Importance of the effective human capital development requires study of techniques of measurement of its value.The goal of the presented research is the furthest development of the conception of Human capital formation in condition of innovative development and social modernization.The authors attempt to calculate the value of human capital for Kazakhstan during last several years on the base of the analyses of different methodological ways of its quantitative and qualitative assessment.As result of the study it was revealed that successful social modernization is not possible without human capital corresponding to international standards in the qualitatively new level.The challenge of human capital development must be formulated as a key task of modernizing of a number of contemporary social sectors - education, culture, health, science, which are considered first of all as a sector capitalization of human potential in Kazakhstan.